2019
DOI: 10.1016/j.msec.2018.10.073
|View full text |Cite
|
Sign up to set email alerts
|

Effects of MgO, ZnO, SrO, and SiO2 in tricalcium phosphate scaffolds on in vitro gene expression and in vivo osteogenesis

Abstract: β-tricalcium phosphate (β-TCP) is a versatile bioceramic for the use in many orthopedic and dental applications due to its excellent biocompatibility and biodegradability. Recently, the addition of additives to β-TCP has been proven to improve bone repair and regeneration, however, the underlying mechanism of enhanced bone regeneration is still unknown. In this study, strontium oxide (SrO), silica (SiO 2 ), magnesia (MgO), and zinc oxide (ZnO) were added to β-TCP for dense discs fabrication followed by in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 35 publications
5
54
0
Order By: Relevance
“…Phosphate is the major ingredient of bone tissue, and is also an important component of commercial bone substitute materials, bone scaffolds, and implant surface coatings [ 5 7 ]. Inorganic phosphate (Pi) in organisms exists in the form of H 2 PO 4 − and HPO 4 2− .Extracellular Pi can stimulate signal transduction and regulate the functions of osteoblasts and stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphate is the major ingredient of bone tissue, and is also an important component of commercial bone substitute materials, bone scaffolds, and implant surface coatings [ 5 7 ]. Inorganic phosphate (Pi) in organisms exists in the form of H 2 PO 4 − and HPO 4 2− .Extracellular Pi can stimulate signal transduction and regulate the functions of osteoblasts and stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…Such parameters were suggested to be superior characteristics for biomolecule loading and releasing [15]. Amongst the different types of ions such as zinc, magnesium and silicon, strontium (Sr) has received a considerable amount of attention in the field of BTE, as it was reported that Sr was able to enhance bone tissue regeneration [16,17]. Of which, it has been proven that Sr was able to simultaneously increase bone formation and decrease resorption.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many multidisciplinary research groups directed their scientific interests toward inorganic antibacterial elements for endowing biomaterials with antibacterial capacity [14,15]. Various kinds of elements such as magnesium [16][17][18], strontium [18,19], silicon [20], zinc [21], lithium [22] and iron [23] have been used as doping elements, which can promote the proliferation and differentiation of osteoblasts. But only limited elements have antibacterial effect, such as silver, copper and zinc.…”
Section: Introductionmentioning
confidence: 99%